2002
DOI: 10.1002/neu.10038
|View full text |Cite
|
Sign up to set email alerts
|

Neural progenitor cells of the neonatal rat anterior subventricular zone express functional GABAA receptors

Abstract: The interneurons of the olfactory bulb arise from precursor cells in the anterior part of the neonatal subventricular zone, the SVZa, and are distinctive in that they possess a neuronal phenotype and yet undergo cell division. To characterize the differentiation of neonatal SVZa progenitor cells, we analyzed the complement of ionotropic neurotransmitter receptors that they express in vitro. For this analysis, we tested the sensitivity of SVZa progenitor cells to gamma-amino-n-butyric acid (GABA), adenosine tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
84
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 57 publications
16
84
2
Order By: Relevance
“…In this study, we show that purified neonatal neuroblasts have large GABAergic currents carried by Cl À with an affinity to GABA comparable with those already reported in postnatal SEZ cells [32,33] and embryonic cortical newborn neurons [34] and that these receptors show benzodiazepine sensitivity. In comparison with neuroblasts, precursors display a lower incidence of GABAergic currents with a much smaller current density, nonetheless modulated by diazepam.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we show that purified neonatal neuroblasts have large GABAergic currents carried by Cl À with an affinity to GABA comparable with those already reported in postnatal SEZ cells [32,33] and embryonic cortical newborn neurons [34] and that these receptors show benzodiazepine sensitivity. In comparison with neuroblasts, precursors display a lower incidence of GABAergic currents with a much smaller current density, nonetheless modulated by diazepam.…”
Section: Discussionsupporting
confidence: 88%
“…In agreement with previous reports (Stewart et al, 2002), we observed that SVZ-derived neurons already expressed different ␣-subunit immunoreactivity (␣ 2,3,4,5) of the GABA A receptors after 1 d in vitro (DIV) (supplemental Fig. 1, available at www.…”
Section: Gaba a Activity Stimulates Dendritic Arbor Development In Easupporting
confidence: 93%
“…The mean resting potential of cells was Ϫ25 Ϯ 3 mV (n ϭ 6 cells) (ranging from Ϫ18 to Ϫ40 mV); we detected no difference between 1 and 6 DIV cells. These results confirmed that SVZ-derived neurons expressed GABA A receptors from early immature stages (Stewart et al, 2002;Carleton et al, 2003).…”
Section: Gaba Depolarizes and Opens L-type Voltage-gated Calcium Chansupporting
confidence: 79%
“…Given that previous works reported the expression of GABA A R in early postnatal neuronal progenitor cells, notably in the anterior subventricular zone, we sought to investigate the presence of these receptors in striatal PSA-NCAM ϩ neuronal precursors (Stewart et al, 2002). To characterize GABA A R subunit transcripts expressed in PSA-NCAM ϩ progenitors, total RNAs extracted from 3-DIV spheres were reverse transcribed, and the subsequent cDNAs were amplified by PCR using specific sets of primers aimed at detecting transcripts for ␣ 1-5 , ␤ 1-3 , ␥ 1-3 , and ␦GABA A R subunit genes (Table 1).…”
Section: Psa-ncam ؉ Spheres Express Type a Gaba Receptorsmentioning
confidence: 99%